2018
DOI: 10.1017/s1431927618000065
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Ionizing Radiation on the Collagen Hierarchical Structure of Bladder and Rectum Visualized by Atomic Force Microscopy

Abstract: Radiation therapy, widely used in the treatment of a variety of malignancies in the pelvic area, is associated with inevitable damage to the surrounding healthy tissues. We have applied atomic force microscopy (AFM) to track the early damaging effects of ionizing radiation on the collagen structures in the experimental animals' bladder and rectum. The first signs of the low-dose radiation (2 Gy) effect were detected by AFM as early as 1 week postirradiation. The observed changes were consistent with initial ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…[ 1 ] about radiation injury on the rectum deserves to be integrated with observations regarding the equivalent damage to the perineal striated muscles. In approaching this topic, not yet extensively studied, we were interested at first in delineating its basic pathology by histological methods, as already proposed [ 2 , 3 ]. For this, we selected from our anatomopathological archive 20 surgical specimens of abdominoperineal resections.…”
mentioning
confidence: 99%
“…[ 1 ] about radiation injury on the rectum deserves to be integrated with observations regarding the equivalent damage to the perineal striated muscles. In approaching this topic, not yet extensively studied, we were interested at first in delineating its basic pathology by histological methods, as already proposed [ 2 , 3 ]. For this, we selected from our anatomopathological archive 20 surgical specimens of abdominoperineal resections.…”
mentioning
confidence: 99%
“…Although AFM is extensively applied in the studies on the ECM of different tissues, no systematic research utilizing AFM has been conducted so far on the radiation-affected human bladder ECM. In our previous study using an animal model [ 25 ], we demonstrated dependence of the early changes in the bladder ECM structure on the radiation dose. Here, we implement this approach to the clinical samples from patients after radiation therapy in addition to a novel quantitative assessment of the ECM structural alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The packing pattern of collagen fibrils at the nanoscale generally repeats that of collagen fibers observed at the microscale (Figure 4a), and the fibrils are covered with an unstructured proteinaceous material (Figure 4f). Such a pattern was present in the animal bladder ECM [25], as well as in certain other types of connective tissue (a "basket-weave" packing of collagen fibers in the skin or arterial walls) [19,32].…”
Section: The Study Of the Ecm At The Level Of Collagen Fibers By Afmmentioning
confidence: 94%
See 1 more Smart Citation
“…Our own experience includes AFM application in tracking characteristic ECM changes in a variety of pathological processes (see, e.g. Kotova et al ., and references therein). Vocal fold ECM has also been studied with AFM, as we mentioned in Introduction (Sivasankar & Ivanisevic, ; Heris et al ., ; Lee et al ., ).…”
Section: Discussionmentioning
confidence: 99%